2020
DOI: 10.1111/cxo.13041
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐regional trends in causes of childhood blindness and low vision in Ghana

Abstract: Background Inter‐regional trends of visual loss in most developing countries remain largely unknown. We compared the causes of childhood blindness among children attending blind schools in the northern (one school) and southern (two schools) regions of Ghana and assessed their need for spectacles and low‐vision devices. Methods Using a standardised methodology, children were examined by an ophthalmologist and optometrists in each location. Causes of visual loss were classified anatomically and by time of onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(27 reference statements)
0
5
2
Order By: Relevance
“…In the present study, the retina ( n = 74, 47.4%) was the most common anatomical site causing vision impairment which is consistent with the trend noted in previous studies involving children in South Africa (Esra & Mayet, 2020; O’Sullivan et al, 1997). This finding differs from other studies where it was noted that the most common site was the lens mostly as a result of cataracts and aphakia in Eritrea ( n = 55, 22.1%) (Gyawali et al, 2017) and Ghana ( n = 75, 29.8%) (Ilechie et al, 2020). A study conducted in India noted that the most common site was the whole globe category mostly as a result of phthisis bulbi and microphthalmos ( n = 83, 32%) (Panda et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, the retina ( n = 74, 47.4%) was the most common anatomical site causing vision impairment which is consistent with the trend noted in previous studies involving children in South Africa (Esra & Mayet, 2020; O’Sullivan et al, 1997). This finding differs from other studies where it was noted that the most common site was the lens mostly as a result of cataracts and aphakia in Eritrea ( n = 55, 22.1%) (Gyawali et al, 2017) and Ghana ( n = 75, 29.8%) (Ilechie et al, 2020). A study conducted in India noted that the most common site was the whole globe category mostly as a result of phthisis bulbi and microphthalmos ( n = 83, 32%) (Panda et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…In an earlier study involving children enrolled in blind schools across South Africa, O’Sullivan et al (1997) reported that corneal scarring attributed to vitamin A deficiency and/or measles infection accounted for avoidable vision impairment in 27 children (5%). The percentage of cases due to corneal opacity/scarring in the present study and previous studies in South Africa are lower than the percentages reported in studies in other developing countries (Gyawali et al, 2017; Gyawali & Moodley, 2017; Ilechie et al, 2020; Panda et al, 2020) (12%–24%) and may reflect the better levels of perinatal care and success of primary health care interventions aimed at measles/rubella immunisation and vitamin A supplementation in South Africa (Baker, 2010; du Plessis et al, 2007).…”
Section: Discussioncontrasting
confidence: 89%
“…In the setting of severe ulceration and perforation from VAD, phthisis bulbi (PB) may also ensue. Given the inter-relatedness of these conditions, several studies combined VAD and measles as a collective cause of vision loss ( 13 , 17 , 19 , 20 ). The proportion of children with blindness due to this combination of VAD and measles ranged between 13.1 and 29% in these studies.…”
Section: Results/findingsmentioning
confidence: 99%
“…Of the 13 studies reviewed, the most common lenticular conditions leading to blindness—“cataract” and “aphakia”—were present in 11 and 5 studies, respectively. Cataract was observed to be an anatomic cause of blindness in 11 studies, leading to blindness from an estimated 7–40% of the VI/BL and notably was the leading cause of blindness in 5 studies ( 12 , 14 , 17 , 18 , 20 ). Patients were referred for surgery in several reports, but the outcomes were not reported in these manuscripts.…”
Section: Results/findingsmentioning
confidence: 99%
See 1 more Smart Citation